Presence: The Core Contextual Factor of Effective Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This article proposes that presence is the core contextual factor of therapeutic effectiveness. Presence is defined as a complex mix of appreciative openness, concerted engagement, support, and expressiveness, and it both holds and illuminates that which is palpably significant within the client and between client and therapist. While the therapeutic alliance, empathy, collaboration, and the provision of meaning and hope have been established as primary contextual factors in the facilitation of effective therapy, this article contends that presence is at their hub. Given that position, it is concluded that although presence is viewed favourably by leading practitioners, there are two major problems with how presence is actually being engaged: The first problem is the way some practitioners are 'using' or 'performing' presence rather than cultivating it as a therapeutic stance, and the second problem is how the training of therapists is becoming increasingly technical at the very time when the research (informing such training) is becoming contextual, relational, and nontechnical.